Joy in Movement: Traditional Sporting Games and Emotional Experience in Elementary Physical Education - Alcaraz-Muñoz, Verónica; Cifo Izquierdo, María Isabel; Gea García, Gemma Maria; Alonso Roque, José Ignacio; Yuste Lucas, Juan Luis (Frontiers in Psychology, 2020)
Through games a motivating learning climate is provided, generating mainly positive emotions among the students by the very nature of the game. However, while the early stages are the most important for emotional well-being development, research about scientific knowledge of emotional physical education in children is still scarce. The aims of this study were to analyse the intensity of emotions (positive or negative) produced when players took part in games of different social structure, with or without competition (winner or loser), with or without sport experience and to examine the explanations given by the participants for these emotional experiences. Participants (N=152) were recruited from 2 Spanish elementary school. We applied Student's t-test and one-factor ANOVA. Students' subjective comments were classified through content analysis in macro-categories and we used the Chi-square Automatic Interaction Detector (CHAID, implemented in SPSS™ Answer Tree© 13.0). The application of a mixed-methods approach identified statistically significant differences in four variables: (a) the type of emotion, (b) motor domain, (c) type of outcome (winning, losing, and non-competitive), and (d) sport experience. The intensity of positive emotions was higher (M=3.71, SD=0.893) than negative emotions (M=1.18, SD=0.253, p<0.001). Furthermore, negative emotions were felt with different intensities (F3=3.82, p=0.011, ES=0.071), depending on the motor action domain. Comments referring to negative emotions were more frequent in individual games. Winning was associated significantly (p<.05) with the highest intensity ratings of positive emotions, whereas losing produced the highest values for negative emotions. The intensity ratings for positive or negative emotions not were different between non-competitive games and competitive games. The sport experience relativizes the mean of emotional intensity, both positive and negative. The present study brings the value of considering games as a key role to promote a physical education addressed to the education of social-emotional well-being in schoolchildren, as the basis of academic training. Furthermore, the results could benefit teachers as well as coaches have scientific input to organize teaching content, generating the desired motor behaviours together with positive experiences.